2
$\begingroup$

let $a,b,c >0 $ and $abc=1$,prove that $\sqrt{1+8a^2}+ \sqrt{1+8b^2}+ \sqrt{1+8c^2}\leq 3(a+b+c )$ can anyone help me with this question. i've tried to assume that $a\geq b \geq c $ as my teacher said,however i couldn't solve it

$\endgroup$
  • 1
    $\begingroup$ can you tell us about your background in inequalities(you know about which inequalities)?are you familiar with AM-GM inequality?what about Cauchy schwarz inequality? $\endgroup$ – user2838619 Aug 3 '14 at 16:06
  • 1
    $\begingroup$ $abc=1$ implies the existence of $x,y,z$ such that $a=x/y,b=y/z,c=z/x$.You could try substitution. $\endgroup$ – rah4927 Aug 3 '14 at 16:27
  • 1
    $\begingroup$ You can find a proof here artofproblemsolving.com/Forum/viewtopic.php?f=151&t=597756 $\endgroup$ – rezvane Aug 3 '14 at 17:35
3
$\begingroup$

Let $$ f(a,b,c)=3\sum_{cyc}a-\sum_{cyc}\sqrt{1+8a^2}.$$ Assuming that $a\geq b\geq c$, the Cauchy-Schwarz inequality gives: $$ f(a,b,c)\geq f(\sqrt{ab},\sqrt{ab},c)\tag{1}$$ hence it is sufficient to prove the inequality in the case $(a,b,c)=\left(x,x,\frac{1}{x^2}\right):$ $$ 3\left(2x+\frac{1}{x^2}\right)-2\sqrt{1+8x^2}-\sqrt{1+\frac{8}{x^4}}\geq 0,$$ $$ 3(2x^3+1)\geq 2x^2\sqrt{1+8x^2}+\sqrt{x^4+8}$$ $$ 1+36x^3-5x^4+4x^6 \geq 4x^2\sqrt{(1+8x^2)(8+x^4)}.\tag{2}$$ To prove $(2)$ it is sufficient to prove that for any $x\in\mathbb{R}^+$ we have: $$ 1+72x^3 - 138x^4 + 2328 x^6 - 360 x^7 \geq 0 \tag{3}$$ or the still weaker: $$ 12-23x+328x^3 \geq 0,$$ $$ f(x)=1-2x+27x^3 \geq 0,\tag{4}$$ that is trivial since that cubic polynomial has a negative discriminant, hence only one real root, and since $f(0)>0$ while $f(-1)<0$ that root is between $-1$ and $0$, so the cubic polynomial is positive over $\mathbb{R}^+$.

$\endgroup$
2
$\begingroup$

WLOG: let $c=\min{(a,b,c)}$,then we have $c\le 1$, use Cauchy-Schwarz inequality we have $$\sqrt{8a^2+1}+\sqrt{8b^2+1}\le\sqrt{(a+b)\left(\dfrac{8a^2+1}{a}+\dfrac{8b^2+1}{b}\right)}=(a+b)\sqrt{c+8}$$ we only prove $$(a+b)(3-\sqrt{c+8})\ge\sqrt{8c^2+1}-3c$$ use AM-GM inequality we have $$(a+b)(3-\sqrt{c+8})\ge 2\sqrt{ab}(3-\sqrt{c+8})=\dfrac{2(3-\sqrt{c+8}}{\sqrt{c}}$$ we only prove $$\dfrac{6}{\sqrt{c}}+3\sqrt{c}\ge 2\sqrt{c+8}+\sqrt{8c^2+1}$$ It is easy prove it

$\endgroup$
0
$\begingroup$

Let $a=e^x$, $b=e^y$ and $c=e^z$.

Hence, $x+y+z=0$ and we need to prove that $\sum\limits_{cyc}f(x)\geq0$, where

$f(x)=3e^x-\sqrt{1+8e^{2x}}$.

But $f''(x)>0$ for all $x>0$.

Thus, by Vasc's RCF Theorem it's enough to prove our inequality for $y=x$ and $z=-2x$

or the starting inequality for $b=a$ and $c=\frac{1}{a^2}$ and the rest is smooth.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.